PKM Tumbuh Kembang Balita di Posyandu Balita Kelurahan Kenali Asam Bawah - Ariyanto Ariyanto; Tina Yuli Fatmawati (Jurnal Abdimas Kesehatan (JAK), 2021)
Growth monitoring is an activity to detect early growth irregularities (malnutrition or poor nutritional status, short children), developmental deviations (late speaking) and mental emotional disorders (impaired concentration and hyperactivity). The purpose of this community service is to increase public knowledge about the normal growth and development of toddlers, increase awareness of mothers about the importance of stimuli for toddler growth and development. The survey that was conducted by the Community Service Team for mothers with toddlers stated that the lack of education provided by posyandu officers, especially regarding toddler growth and development. The method used in community services is discussion, question and answer, and weight checks on toddlers. The service was carried out at the Beringin Posyandu in Kenali Asam Bawah for mothers who have toddlers, implemented in December 2019-January 2020. After counseling activities, participants who attended understood about how to monitor growth and development in toddlers and can monitor ideal weight in toddlers